The Effect of Auditor Ethics, Auditor Experience, Audit Fees, and Auditor's Motivation on Audit Quality (Case study of a Public Accounting Firm in Semarang) - Mulyani, Ika (MALIA: Journal of Islamic Banking and Finance, 2019)
The purpose of this paper is to identify the effect of Auditor Ethics, Auditor Experience, Audit Fees, and Auditor’s Motivation on Audit Quality.The population of this research is the Auditor at the Public Accountant Office in Semarang. The sampling technique uses Simple Random Sampling. The data used in this study are primary data taken by distributing questionnaires. The analysis model uses multiple linear regression analysis models, while the analysis technique uses the Statistical Test F, the Coefficient of Determination (, and the Statistical test t.The results of the analysis and discussion showed that the auditor's ethical variables, auditor's experience, audit fees, and auditor's motivation simultaneously had a significant effect on audit quality. Auditor ethics, auditor experience, and Auditor Motivation on the quality of each audit partially significant effect on audit quality. Whereas Audit Fee partially has no significant effect on Audit Quality.